Synthesis of Pt–Cu Nanodendrites through Controlled Reduction Kinetics for Enhanced Methanol Electro‐Oxidation. Issue 10 (17th September 2013) - Taylor, Eric; Chen, Shutang; Tao, Jing; Wu, Lijun; Zhu, Yimei; Chen, Jingyi
<x xml:space="preserve">Abstract</x> Final reductions: Alloyed Pt–Cu nanodendrites are synthesized through a two‐step co‐reduction method, in which the reduction rate is controlled by the oxidative etchants and the reducing agents. These dendritic nanostructures are the result of overgrowth along the <111> axis of the face‐centered cubic structure and the coalescence of small dendritic seeds. These nanodendrites are highly active for methanol electro‐oxidation because of their unique structure and the bifunctionality of Pt and Cu.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>